2020
DOI: 10.3390/molecules25051195
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Aggregation Mechanisms in Amyloids

Abstract: The aggregation of a polypeptide chain into amyloid fibrils and their accumulation and deposition into insoluble plaques and intracellular inclusions is the hallmark of several misfolding diseases known as amyloidoses. Alzheimer′s, Parkinson′s and Huntington’s diseases are some of the approximately 50 amyloid diseases described to date. The identification and characterization of the molecular species critical for amyloid formation and disease development have been the focus of intense scrutiny. Methods such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
118
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 163 publications
(121 citation statements)
references
References 292 publications
(307 reference statements)
3
118
0
Order By: Relevance
“…At the early stages of the oligomerization process (15 h of incubation), the SDS-PAGE gels showed that the most abundant species were 1-mers (22.2% and 21.5% for TTRV30M and TTRL55P, respectively, compared to 33.0% for TTRwt) and 2-mers (32.0% and 28.2% for TTRV30M and TTRL55P, respectively, compared to 29.2% for TTRwt), with TTRL55P showing higher amounts of larger-sized oligomers (>3-mers) and HMW species ( Figure 2). Nonetheless, regardless of the protein variant and oligomerization kinetics, the same pattern of linear polymerization was observed for the three TTR variants, suggesting a downhill polymerization type of oligomerization mechanism through multiple sequential steps, with successive addition of monomeric subunits (1-mers) to the growing low-molecular-weight (LMW) oligomer [55], at least until the formation of octamers (8-mers) [9]. Additionally, in order to characterize the nature and morphology of the TTR aggregates formed, we have analyzed the samples by thioflavin-T (ThT) extrinsic fluorescence and transmission electron microscopy (TEM).…”
Section: Early Oligomerization Of the Amyloidogenic Variants Ttrv30m mentioning
confidence: 83%
See 4 more Smart Citations
“…At the early stages of the oligomerization process (15 h of incubation), the SDS-PAGE gels showed that the most abundant species were 1-mers (22.2% and 21.5% for TTRV30M and TTRL55P, respectively, compared to 33.0% for TTRwt) and 2-mers (32.0% and 28.2% for TTRV30M and TTRL55P, respectively, compared to 29.2% for TTRwt), with TTRL55P showing higher amounts of larger-sized oligomers (>3-mers) and HMW species ( Figure 2). Nonetheless, regardless of the protein variant and oligomerization kinetics, the same pattern of linear polymerization was observed for the three TTR variants, suggesting a downhill polymerization type of oligomerization mechanism through multiple sequential steps, with successive addition of monomeric subunits (1-mers) to the growing low-molecular-weight (LMW) oligomer [55], at least until the formation of octamers (8-mers) [9]. Additionally, in order to characterize the nature and morphology of the TTR aggregates formed, we have analyzed the samples by thioflavin-T (ThT) extrinsic fluorescence and transmission electron microscopy (TEM).…”
Section: Early Oligomerization Of the Amyloidogenic Variants Ttrv30m mentioning
confidence: 83%
“…TTR is implicated in several acquired and hereditary amyloid pathologies (ATTR, TTR amyloidosis) [1,8,9]. Whereas wild-type TTR (TTRwt) is associated with acquired amyloidosis with mainly cardiac involvement (ATTRwt) [10], different variants of TTR are the cause of hereditary amyloidosis involving the peripheral nervous system, autonomic nervous system, heart, eye, leptomeninges and vasculature of the brain [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations